1975
DOI: 10.1001/archpedi.1975.02120400075020
|View full text |Cite
|
Sign up to set email alerts
|

Mesomelic Dwarfism as the Homozygous Expression of Dyschondrosteosis

Abstract: Pedigree analysis in this kindred is compatible with an autosomal dominant inheritance. The parents and three other family members have clinical and radiological features of dyschondrosteosis. The two propositi, a boy and a girl, have mesomelic dwarfism and hypoplasia of the mandible, ulna, and fibula. It is our interpretation that mesomelic dwarfism is the clinical manifestation of the homozygous state for dyschondrosteosis. Mesomelic dwarfism is character¬ ized by short stature caused primarily by reductions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…Léri-Weill syndrome (dyschondrosteosis) represents a short stature condition characterized by a symmetric shortening of the forearms and lower legs, and a bilateral shortening and bowing of the radius with a dorsal subluxation of the distal ulna (Madelung deformity) [10,11]. According to the clinical description, Langer's type of mesomelic dysplasia has been suggested to represent the homozygous form of Léri-Weill dyschondrosteosis [12][13][14]. Despite a prevalence of affected women [15], the syndrome was originally suggested to be inherited in an autosomal dominant manner.…”
Section: Shox In Léri-weill Syndromementioning
confidence: 99%
“…Léri-Weill syndrome (dyschondrosteosis) represents a short stature condition characterized by a symmetric shortening of the forearms and lower legs, and a bilateral shortening and bowing of the radius with a dorsal subluxation of the distal ulna (Madelung deformity) [10,11]. According to the clinical description, Langer's type of mesomelic dysplasia has been suggested to represent the homozygous form of Léri-Weill dyschondrosteosis [12][13][14]. Despite a prevalence of affected women [15], the syndrome was originally suggested to be inherited in an autosomal dominant manner.…”
Section: Shox In Léri-weill Syndromementioning
confidence: 99%
“…Within the "mesomelic dysplasia-syndromes", the Langer type with defective ossification of the distal ulna and p r o x i m a l fibula is a fully established clinical entity (Beighton 1978;Espiritu et al 1975;Fryns and Van den Berghe 1979;Blockey and Lawrie 1963;Langer 1965;Silverman 1973). In our case the radiologic investigation confirmes the clinical impression of mesomelic micrometia.…”
Section: Family Studymentioning
confidence: 99%
“…Silverman (1973), Espiritu et al (1975), and recently Fryns and Van den Berghe (1979) reported infants with mesomelic dysplasia, type Langer, in whom both parents were clearly affected by dyschondrosteosis. Their conclusions favor the concept of a homozygous state of the dyschondrosteosis gene in mesomelic dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of marked shortness of the mesomelic parts and retrognathia was reported in individuals with Langertype mesomelic dwarfism [Langer, 1967]. This condition is the homozygous state of dyschondrosteosis [Espiritu et al, 1975] and is hence ruled out in Mrs. Vance because of her family history. Daffner [1898] made the diagnosis of ''a maternally inherited malformation of the forearms and the shanks.''…”
Section: Discussion Alice Vance: a Historical Case Of Nievergelt Syndmentioning
confidence: 99%